CRISPR‐Act3.0‐Based Highly Efficient Multiplexed Gene Activation in Plants. Issue 2 (14th February 2022) - Pan, Changtian; Qi, Yiping
Abstract: CRISPR/Cas (clustered regularly interspaced short palindromic repeats/CRISPR‐associated protein)‐mediated genome editing has revolutionized fundamental research and plant breeding. Beyond gene editing, CRISPR/Cas systems have been repurposed as a platform for programmable transcriptional regulation. Catalytically inactive Cas variants (dCas), when fused with transcriptional activation domains, allow for specific activation of any target gene in the genome without inducing DNA double‐strand breaks. CRISPR activation enables simultaneous activation of multiple genes, holding great promise in the identification of gene regulatory networks and rewiring of metabolic pathways. Here, we describe a simple protocol for constructing a dCas9‐mediated multiplexed gene activation system based on the CRISPR‐Act3.0 system. The resulting vectors are tested in rice protoplasts. © 2022 Wiley Periodicals LLC. Basic Protocol 1 : sgRNA design and construction of CRISPR‐Act3.0 vectors for multiplexed gene activation Basic Protocol 2 : Determining the activation efficiency of CRISPR‐Act3.0 vectors using rice protoplasts